2022
DOI: 10.5539/jas.v14n2p122
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Attributed Parametric Review Study on Mechanical Cotton (Gossypium hirsutum L.) Harvesters

Abstract: Crop characteristics of cotton are crucial to identify the important crop attributes like plant height, canopy width, sympods and monopods distribution, row spacing which affects the performance of mechanical harvesters. The activity and effectiveness of most harvest aids, including desiccants is reduced by low temperature conditions. Trash content was observed to be lesser in cotton harvested by cotton picker than cotton harvested by cotton stripper. It was found that a maximum cotton yield of 1000 kg acre-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The choice of cotton variety and their characteristics of the crop, such as plant height, canopy width, number of branches, boll dimensions, and bracts angle, signi cantly in uence the performance of cotton pickers (Nowrouzieh et al, 2022). Similarly, different plant spacing can affect growth parameters, yield attributes, and seed cotton yield and play a crucial role in determining the performance of mechanical harvesters (Rupinder and Karun, 2022;Khadija et al, 2022). Studies have shown that the use of mepiquat chloride can signi cantly impact plant morphological traits, yield improvement, and ber quality in cotton, leading to enhanced harvesting e ciency (Dharani et al, 2022; Uma Maheswari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of cotton variety and their characteristics of the crop, such as plant height, canopy width, number of branches, boll dimensions, and bracts angle, signi cantly in uence the performance of cotton pickers (Nowrouzieh et al, 2022). Similarly, different plant spacing can affect growth parameters, yield attributes, and seed cotton yield and play a crucial role in determining the performance of mechanical harvesters (Rupinder and Karun, 2022;Khadija et al, 2022). Studies have shown that the use of mepiquat chloride can signi cantly impact plant morphological traits, yield improvement, and ber quality in cotton, leading to enhanced harvesting e ciency (Dharani et al, 2022; Uma Maheswari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying causes behind the improvement observed in the study with the application of these compounds on cotton production during drought stress are not specified in the existing literature and have yet to be thoroughly investigated. However, potential explanations for the enhancements in cotton boll seed weight, the yield of seed cotton, boll numbers, and ginning turnout percentage might include boosted plant growth and development, a reduction in premature flower and boll drop, and an enhancement in photosynthesis activity (Chandel & Sharma, 2022; Shaukat et al, 2021). The application of both compounds in combination showed a significant improvement in various agronomic characteristics, which may be a result of their synergistic effect working together to enhance plant growth and development, reduce flower and boll drop, and improve photosynthesis activity (Shavkiev et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the raw materials in the production of cotton spinning enterprises have a comparatively low ignition point, which may lead fire [1,2]. For example, the ignition point of cotton is 210 • C, and cotton fiber in a loose state is only 150 • C, which burns 15% to 26% faster than wood [3,4]. Especially in the production sites of textile enterprises, there are widely scattered and loose cotton, cotton rolls and cotton slivers.…”
Section: Introductionmentioning
confidence: 99%